Sex ratio estimation for Green Turtle, Chelonia mydas, hatchlings at Akyatan Beach, Turkey. Issue 4 (2nd October 2022) - Yılmaz, Can; Oruç, Ayşe
Abstract : Marine turtles have temperature-dependent sex determination and the increase in global temperature could cause female predominance due to higher nest temperatures. The temperatures of 163 Green Turtle nests were measured with temperature data loggers at Akyatan beach, Turkey. The mean entire incubation duration (EID) and the sexdetermination period (SPD) temperatures of the Green Turtle nests were 31.03°C and 30.81°C respectively. The mean incubation duration (ID) was 51.94 days. Significant differences were found in terms of ID among nesting seasons, and ID had a negative relationship with the nesting seasons. The mean ID for the nesting seasons had a statistically significant negative correlation with EID temperature. The mean female ratio estimation for the nesting seasons was 89%. Significant differences were found among the female ratio estimations for the nesting seasons. The mean female ratio estimation for the nesting seasons showed a statistically significant negative correlation with ID and nest depth. Long-term temperature increase may pose a threat to the Green Turtle populations.